Variations of Social Pedagogy - Explorations of the Transnational Settlement Movement - Stefan Koengeter; Wolfgang Schroeer (Arizona State University, 2013)
Both the German and the international discourses on social pedagogy are shaped by a diachronic perspective on its history, which takes nationally differing developments as its starting point as a matter of course, and thus sees socio-pedagogical thinking as having its roots in particular nation states. In our article, however, we wish to take a synchronic, transnational perspective, and to show, by means of the transnational development of the settlement movement, that a socio-pedagogical constellation has developed transnationally. After considering examples of the transnational development of the settlement movement in the USA, Germany and Canada, we will reconstruct variants of socio-pedagogical thinking using key publications from the settlement movements. Rather than focusing on historical attempts at definition undertaken by those regarded as the classic proponents of social pedagogy, this essay is concerned with identifying a socio-pedagogical constellation within which various definitions are present synchronically, and can always be read from various intersections of national, disciplinary, theoretical etc. positionings. The socio-pedagogical constellation, as we derive it from the transnational settlement movement, concentrates on the relationship between a diagnosis of social conditions, the pedagogical organization of social relations, and the expansion of normatively defined agency. This trilateral socio-pedagogical constellation is presented at the end of the essay and positioned in relation to other socio-pedagogical attempts at definition.